(3ebGdI aj GdMUGI hGdcdi hGdeKGfIs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3jbhd ai GdMUdI GdJi ai Gdcdi bhdG hLjRkG hGVMG ZjQ eThH HPcQ SHH HYjO hdG jMH WHjYI dcf HebOGQ eG VWQ Edjg GdeYGdL ef gPG GdOGA abW s
(3BNQgG (B:s
(3CYQGV GdMUGI ai GdeKGfI UaI OhGA jMbf Hg GdEMdjd aJdMe GdbQhM GdWQjI , CSajOGL GdQUGU s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B244 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3HGJGajG (B(585) s
Keywords: (3GdWHs